The kondi of Sierra Leone - van Oven, Cootje (International Library of African Music, 1973)
The very title of this article needs a small measure of justification. It has been used because it would have been too cumbersome to call the article 'The kangdi or kututen or bundoma of Sierra Leone'. The instrument is played by Temne, Limba and Loko musicians who call it by those three names respectively. But the word kongdi, obviously based on the Temne name, is understood intertribally and I have even met Limba musicians who appeared to know the word kongdi better than kututen.
Keywords: African Music; Sierra Leone